PENGARUH PELATIHAN TENTANG PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) ANAK USIA PRA SEKOLAH TERHADAP PENGETAHUAN GURU DI PG/TK NAKITA INSAN MULIA PURWOKERTO - Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2017)
Background : When a child is injured, parents and teachers are panicked and do not know what to do. There are some who provide the usual help (such as topical oil), although they do not know whether this is true or not, from a medical-health perspective. Improper first handling such as injuries that are not treated properly, then it could potentially be more severe injuries. Even feared can be a germ infects the wound and spread throughout the body, so that harm. First aid at school is temporary relief and care to the victim at school before being taken to a hospital, health center or health clinic for better help from doctors or paramedics First aid is intended to appease and calm the patient before being handled by more skilled personnel with a more adequate means. Expected with a more calm can reduce the pain of the patient. Therefore, the knowledge of first-aid accidents in pre-school age children is needed by caregivers and PAUD teachers to be able to handle properly. Objective: To analyze the knowledge of PG/TK teacher Nakita Insan Mulia Purwokerto on First Aid on Child Accident (P3K) before and after training Method : This research uses quantitative research type. The research design is pre-experimental design with one - group pretest - posttest design approach. Sample amounted to 19 taken with total sampling technique. Results : 1) The description of the knowledge of the PG/TK teacher Nakita Insan Mulia Purwokerto on first aid in the crash (P3K) before the training is mostly in the sufficient category of 11 people (57.9%) and a small part in the good category ie 2 people (10.5% ) and a small in enough category that is as much as 1 person (18%); 2) The description of PG/TK teacher's knowledge of Nakita Insan Mulia Purwokerto on first aid in accident after first training is mostly in good category (18 persons (57.9%); and (3) There was a significant difference between teacher's knowledge in PG/TK Nakita Insan Mulia Purwokerto between before and after training with p value of 0.000 (<0,05). Conclusion: 1) The description of PG/TK teacher's knowledge of Nakita Insan Mulia Purwokerto on first aid in accident (P3K) before training is mostly in enough category that is 11 people (57.9%); 2) The description of PG / TK teacher's knowledge of Nakita Insan Mulia Purwokerto on first aid in accident after first training is mostly in good category (18 persons (57.9%); and (3) There was a significant difference between teacher's knowledge in PG / TK Nakita Insan Mulia Purwokerto between before and after training with p value of 0.000 (<0,05). Keywords: training, knowledge, first aid in accidents